German physicians' expectations of healthcare management companies: An exploratory study - Dirk Oberschachtsiek; Andree Ehlert (Health Science Reports, 2022)
Abstract Background and aims Even 20 years after the introduction of managed care (MC) in Germany, many physicians are skeptical of the concept, hindering its acceptance. Methods Based on multivariate statistical methods this exploratory study examines how so‐called management companies, that is, administrative service providers within MC contracts, can increase physicians' acceptance of MC by offering, for example, day‐to‐day coordination and administrative tasks. Results As a main empirical result, we find support for this hypothesis, that is, that certain physicians evaluate their MC participation according to its prospective administrative support. Based on this, up to four clusters of physicians can be statistically identified in terms of their preferences regarding MC. Conclusion As a policy recommendation, we derive from our results that a future focus on the administrative support components of MC is essential to attract certain physician groups to participate in MC.